Gender Differences and Psychopathological Features Associated With Addictive Behaviors in Adolescents - Di Nicola, Marco; Ferri, Vittoria Rachele; Moccia, Lorenzo; Panaccione, Isabella; Strangio, Annamaria Miriam; Tedeschi, Daniela; Grandinetti, Paolo; Callea, Antonino; De-Giorgio, Fabio; Martinotti, Giovanni; Janiri, Luigi (Frontiers in Psychiatry, 2017)
Background. The aims of the study were to assess prevalence and gender differences of addictive behaviors (substance- and non-substance-related) in an adolescent population, and their association with psychopathological features and academic performance. Material and methods. A sample of high school Italian students (n=996; M=240, F=756) was examined using a self-report survey concerning socio-demographic characteristics, cigarette smoking, alcohol and substance use, perceived academic performance, activities and behaviors (Internet use, gambling, physical exercising). The Internet Addiction Test (IAT), the South Oaks Gambling Screen - revised Adolescents (SOGS-rA), the Exercise Addiction Inventory - Short Form (EAI-SF) were administered to identify problematic behaviors. The Barratt Impulsiveness Scale Adolescent Version (BIS-11-A), the Snaith-Hamilton Pleasure Scale (SHAPS), the Dissociative Experience Scale for adolescents (A-DES), the Toronto Alexithymia Scale (TAS-20) were used to investigate psychopathological dimensions. Results. Frequent alcohol intake and lifetime substances consumption were more common among males. The occurrence of other addictive behaviors was: 22.1% for problematic Internet use (M=F), 9.7% for at risk/problematic gambling (M>F), 6.2% for maladaptive physical exercise (M=F). We also found an association between substance-/non-substance-related addictive behaviors and psychopathological dimensions. Addictive behaviors were more frequent among students reporting poor school performance. Conclusions. Our study showed a relevant prevalence of addictive behaviors in a sample of Italian high school students, with specific gender differences. We underlined the co-occurrence of substance and non-substance-related addictive behaviors, and their association with worse school performance. Dissociative proneness, anhedonia, alexithymia, and impulsivity were associated with addictive behaviors in adolescents, and might represent vulnerability factors for the development of psychiatric disorders in adulthood. A better understanding of psychopathological features associated with addictive behaviors might be useful for the prevention/early intervention.